MANAJEMEN PESERTA DIDIK BERPRESTASI MELALUI PENDEKATAN SPIRITUAL - Hakim, Lukmanul; Ridhlo, M. Rasyid (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2023)
The focus of the research is limited to the management process of outstanding students through a spiritual approach and the evaluation model used. The purpose of this study was to find a model of the management function of outstanding students through a spiritual approach. The coaching program is carried out by carrying out management functions appropriately and professionally by empowering all educational resources in the process of achieving educational goals effectively and efficiently. The form of coaching is through the integration of spiritual values ​​into students' subjects which aims to shape the character of students as a whole. This research was conducted at SMPN 5 Mataram using qualitative research methods. Research data in the form of: descriptive data collected through interviews, documentation, and participatory observation. The results of the research achieved are in the form of a model for managing outstanding students through a spiritual approach which later can also be used as guidance for guidance for all public junior high schools in the city of Mataram in particular and public junior high schools in NTB in general